Apigenin, an Anticancer Isolated from Macaranga gigantifolia Leaves - Fajriah, Sofa; Megawati, Megawati; Darmawan, Akhmad (Journal of Tropical Life Science, 2016)
Apigenin, a flavonoid compound has been isolated from the ethyl acetate fraction of methanol extract of Macaranga gigantifolia leaves. Isolation and purification of apigenin conducted using chromatographic method, and chemical structure characterized based on spectroscopic data. In vitro anticancer activity test against murine leukemia P-388 cell line showed potential activity with IC50 14.13 Î¼g/mL.Key words: apigenin, flavones, Macaranga gigantifolia, anticancer, murine leukemia P-388 cell line.